Pedagogical Knowledge and Teaching Career Interest as Predictors of Microteaching Learning Outcomes among Electrical EngineeringEducation Students - Virliana Sabrina; Darlan Sidik; Hasanah Nur (Fakultas Teknik, Universitas Negeri Makassar, 2026)
Purpose – This study aimed to examine the influence of pedagogical knowledge and interest in becoming a teacher on microteaching learning outcomes among Electrical Engineering Education students. Methods – This research employed a quantitative ex post facto design involving 70 students who had completed the microteaching course. The sample was determined using a total sampling technique. Data were collected through questionnaires measuring pedagogical knowledge and interest in becoming a teacher, while microteaching learning outcomes were obtained from students’ academic performance records. Data were analyzed using descriptive statistics and multiple linear regression analysis. Findings – The results revealed that pedagogical knowledge and interest in becoming a teacher did not have a significant partial effect on microteaching learning outcomes. However, both variables simultaneously had a significant effect on learning outcomes (p < 0.05). The coefficient of determination indicated that the regression model explained only 9% of the variance in microteaching learning outcomes (R² = 0.09; Adjusted R² = 0.07), suggesting that other factors outside the model contributed more substantially to student performance. Research Implication – These findings indicate that although pedagogical knowledge and teaching career interest collectively contribute to microteaching learning outcomes, their contribution remains limited. Therefore, improving microteaching performance requires integrating pedagogical understanding with practical teaching skills, reflective practice, and structured instructional feedback. Originality – This study provides empirical evidence that pedagogical knowledge and interest in becoming a teacher have a significant simultaneous effect, but not a significant partial effect, on microteaching learning outcomes among Electrical Engineering Education students.